Development of Natural Sciences Module with Reflective Learning Journal to Enhance Student’s Reporting-Interpretative Skills - Hadaina Zulfah; Nurfina Aznam (Biosaintifika: Journal of Biology & Biology Education, 2018)
One of the successful factors of the curriculum 2013 implementation is the availability of appropriate and relevant teaching materials. Teaching materials can be textbooks, interactive videos , virtual labs, maket and so on. Unfortunately, there are still found many materials that are less in accordance with the curriculum of 2013. Therefore it should be developed a more appropriate teaching materials, one of them is a natural sciences module with reflective learning journal. The development of natural sciences modulewas done with research that aims to develop and analyze the effectiveness of natural sciences modulewith reflective learning journals. This research was an RD research using development research procedure according to Thiagarajanthat known as 4D (define, design, develop and dessiminate). The data collection was done by test and non-test technique. Instrument that used in non test technique are interview guides, product validation sheet, students’ response sheet to the readability of science nature modul with reflective learning journal., meanwhile the instrumen that used in test technique is essay question with reporting-interpretative skills’s indicators. The results showed that the leligibility of the natural sciences module with reflective learning journal was categorized as approriate and effective to improve student’s reporting-interpretative skills.